The healthcare burden of hypertension in Asia. Issue 1 (19th November 2013) - Jin, Chun-Na; Yu, Cheuk-Man; Sun, Jing-Ping; Fang, Fang; Wen, Yong-Na; Liu, Ming; Lee, Alex Pui-Wai
Abstract : As the leading global risk for mortality, hypertension (HT) is a common healthcare problem in the world. The total number of patients with HT is likely to grow in the next few decades as the population age and the prevalence of obesity and diabetes increase. HT, as a major modifiable risk factor for cardiovascular disease, results in more deaths than any other risk factors, including diabetes and cigarette smoking. High prevalence, inadequate awareness, suboptimal treatment and low rate of achieving guideline-recommended target blood pressure control are key factors leading to severe cardiovascular complications that impose a heavy socioeconomic burden, especially in developing countries. Asia is the world's largest and most populous continent with approximately 4.3 billion people, hosting 60% of the world's current human population, and has a high growth rate. Asia differs very widely from the West with regard to ethnic groups, cultures, environments, economics, historical ties and government systems. Therefore, the purpose of this review is to comprehensively summarise the epidemiology, treatment practice and the status of control of HT in different Asian countries in order to guide the future prevention and management in this part of the world.